2014
DOI: 10.1016/j.neuroimage.2014.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Age-related effects in the neocortical organization of chimpanzees: Gray and white matter volume, cortical thickness, and gyrification

Abstract: Among primates, humans exhibit the most profound degree of age-related brain volumetric decline in particular regions, such as the hippocampus and the frontal lobe. Recent studies have shown that our closest living relatives, the chimpanzees, experience little to no volumetric decline in gray and white matter over the adult lifespan. However, these previous studies were limited with a small sample of chimpanzees of the most advanced ages. In the present study, we sought to further test for potential age-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 79 publications
5
30
1
Order By: Relevance
“…Therefore, even though we did not find an increase in the number of astrocytes labeled for GFAP, we cannot definitively state that the overall amount of this protein does not change with age. However, although our methods are limited, the results of this study are consistent with earlier reports that found differences between humans and chimpanzees in brain aging (Autrey et al, ; Chen et al, ; Sherwood et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, even though we did not find an increase in the number of astrocytes labeled for GFAP, we cannot definitively state that the overall amount of this protein does not change with age. However, although our methods are limited, the results of this study are consistent with earlier reports that found differences between humans and chimpanzees in brain aging (Autrey et al, ; Chen et al, ; Sherwood et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The limitation of this theory is that directional asymmetries are present and can vary between species . Indeed, we have previously found that chimpanzees show a small but significant leftward asymmetry in gyrification . Likewise, we have previously found that chimpanzees show a leftward asymmetry in the gray matter volume of the p_STG, but neither macaques nor vervet monkeys show a group‐level bias .…”
Section: Mechanisms Underlying the Evolution Of Behavioral And Brain mentioning
confidence: 90%
“…The animal was humanely killed because of myocarditis (heart failure). The neocortex is expected to have few age-related changes in a chimpanzee of this age (51,52). Shortly before death, her body weight was 34.8 kg.…”
Section: Methodsmentioning
confidence: 99%